Penatalaksanaan Neuro Development Treatment (NDT) Pada Kasus Cerebral Palsy Spastik Quadriplegi Di Pntc (Pediatric And Neurodevelopmental Teraphy Centre ) - Prahesti Libryani, Diaz; , Umi Budi Rahayu S.Fis. S.Pd, M.Kes (2015)
Background: Cerebral Palsy Spastic quadriplegia is a disorder of child development due to the disruption of movement and posture that is not progressive in the brain before, during and after birth are characterized by paralysis of the neck, body and all four extremities with increased physiological endurance muscle passive motion. Implementation of this case study was conducted in PNTC using exercise therapy for six times the therapy, the authors hereby wish to know the problems that arise in these conditions. Objective: The implementation of this therapy aims to determine the effect of therapy Neuro Development Treatment in reducing spasticity and improve functional ability on the condition Spastic quadriplegia cerebral palsy. Methods: This study is a case study conducted to DT with Cerebral Palsy Spastic quadriplegia cases in PNTC, on January 29, 2015 by using Neuro Development Treatment (NDT). This method of dealing with the quality of not only the pattern of coordination and motoric sensory problems, but also problems of development, emotional problems, decreased cognitive perception, social and functional of everyday life. Results: Treatment with exercise therapy Neuro Development of Treatment methods: 1) there is no impairment of spasticity in the upper limbs and lower limbs T1 value of 2, 2 in measuring the value T6 with scale asworth, 2) no increase in functional ability on the dimensions of A, B, C, D, and E were measured with the Gross Motor Functional Measure (GMFM). Conclusion: The exercises are only given 6x consecutive week with a duration of 30 minutes a day does not have any significant impact on the patient's motor planting.